2014
DOI: 10.1073/pnas.1412099111
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the sodium-coupled neutral amino acid transporter (SNAT2) by 17β-estradiol

Abstract: The sodium-coupled neutral amino acid transporter 2 (SNAT2) translocates small neutral amino acids into the mammary gland to promote cell proliferation during gestation. It is known that SNAT2 expression increases during pregnancy, and in vitro studies indicate that this transporter is induced by 17β-estradiol. In this study, we elucidated the mechanism by which 17β-estradiol regulates the transcription of SNAT2. In silico analysis revealed the presence of a potential estrogen response element (ERE) in the SNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…However, among them, only a small number have been shown to possess functional EREs within the transcription regulatory region. In mammals, these genes include transcription factors, such as JUN [32] , FOS [33] , PGR [34] , and TP53 [35] , intracellular signaling molecules, such as HRAS [36] , BCL2 [37] , and BRCA1 [38] , enzymes, such as CHAT [39] , NQO1 [40] , and CKB [41] , secreted proteins, such as LTF [42] , SCGB1A1 [43] , OVGP1 [44] , C3 [45] , and AGT [46] , hormones, such as LHB [47] , OXT [48] , PRL [49] , and AVP [50] , membrane proteins, such as SNAT2 [51] and VEGFA [52] , the motogen TFF1 [53] , and the protease CTSD [54] . These genes are assumed to directly mediate various estrogen actions in normal tissues, as well as in cancer and other diseases.…”
Section: Steroid Hormone Target Genes and The Transcription Cascadementioning
confidence: 99%
“…However, among them, only a small number have been shown to possess functional EREs within the transcription regulatory region. In mammals, these genes include transcription factors, such as JUN [32] , FOS [33] , PGR [34] , and TP53 [35] , intracellular signaling molecules, such as HRAS [36] , BCL2 [37] , and BRCA1 [38] , enzymes, such as CHAT [39] , NQO1 [40] , and CKB [41] , secreted proteins, such as LTF [42] , SCGB1A1 [43] , OVGP1 [44] , C3 [45] , and AGT [46] , hormones, such as LHB [47] , OXT [48] , PRL [49] , and AVP [50] , membrane proteins, such as SNAT2 [51] and VEGFA [52] , the motogen TFF1 [53] , and the protease CTSD [54] . These genes are assumed to directly mediate various estrogen actions in normal tissues, as well as in cancer and other diseases.…”
Section: Steroid Hormone Target Genes and The Transcription Cascadementioning
confidence: 99%
“…Recently, it has been demonstrated that upregulation of SNAT2 gene expression during gestation is mediated by the estrogen receptor α bound to the coactivator glyceraldehyde 3-phosphate dehydrogenase that specifically binds to an estrogen response element found in the SNAT2 gene promoter [13]. Interestingly, we have evidence that after gestation, there is a second increase of SNAT2 mRNA that reaches its maximal in the peak of lactation in the mammary gland [12].…”
Section: Introductionmentioning
confidence: 57%
“…Previous studies showed that the expression of SNAT2 was increased in ER+ positive breast cancer cell lines after 17β-estradiol (E 2 ) stimulation and an estrogen response element (ERE) was described in the SNAT2 promoter in rat mammary glands during gestation (31, 32). Because hypoxia is related to adverse outcome in tamoxifen-treated breast cancer patients (14) and SNAT2 was among the 202 genes bound by HIF-1α and ERα and regulated by fulvestrant (14), we investigated the regulation of SNAT2 expression by estrogen and hypoxia in ER+ breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%